2009
DOI: 10.1002/ddrr.59
|View full text |Cite
|
Sign up to set email alerts
|

Constraint‐induced movement therapy (CIMT): Pediatric applications

Abstract: The purpose of this article is to describe theoretical and research bases for constraint‐induced movement therapy (CIMT), to discuss key features and variations in protocols currently in use with children, and to review the results of studies of efficacy. CIMT has been found to be an effective intervention for increasing functional use of the hemiparetic upper extremity in adults with chronic disability from stroke. CIMT developed out of behavioral research on the phenomenon of “learned nonuse” of an upper ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Stem cell implantation combined with EE and therapies directed at attenuating neuroinflammation produced the highest number of successes and thus these viable promising approaches warrant continued research. Other non-pharmacological therapies that have shown some success when provided singly include electrical and magnetic brain stimulation (Li et al, 2015; Zhang et al, 2015; Clayton et al, 2016), constrained-induced movement therapy (Brady and Garcia, 2009) and low-level laser therapy (Oron et al, 2012; Xuan et al, 2013) and may potentially be more effective when augmented by a secondary therapy. Lastly, it is important that potential therapies be evaluated by several independent groups so that the results are replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell implantation combined with EE and therapies directed at attenuating neuroinflammation produced the highest number of successes and thus these viable promising approaches warrant continued research. Other non-pharmacological therapies that have shown some success when provided singly include electrical and magnetic brain stimulation (Li et al, 2015; Zhang et al, 2015; Clayton et al, 2016), constrained-induced movement therapy (Brady and Garcia, 2009) and low-level laser therapy (Oron et al, 2012; Xuan et al, 2013) and may potentially be more effective when augmented by a secondary therapy. Lastly, it is important that potential therapies be evaluated by several independent groups so that the results are replicated.…”
Section: Discussionmentioning
confidence: 99%
“…However, we expected that it would be difficult for pediatric patients to complete the program for lack of stamina and difficulty in persistent concentration on the task. Indeed, Brady et al [24] have already suggested that the original protocol of constraint-induced movement therapy (CIMT) was troublesome and not accepted by pediatric patients. Therefore, we modified the intensive OT protocol for pediatric patients by shortening the training time, providing therapy in the home environment, and partly camouflaged the therapy within the context of play.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the patient engages in task-specific movements, known as shaping, which could be the grasping of a coffee cup [23]. Another popular technique is called constraint-induced movement therapy (CIMT) [27], and it consists of restraining the unaffected limb to promote the use of the affected one. This can ultimately lead to faster and improved movement of the affected limb.…”
Section: Conventional Stroke Therapymentioning
confidence: 99%